ANALISIS FILOGENETIK MANGGA (MANGIFERA SPP.) BERDASARKAN GEN 5,8S RRNA - Olivia Anafarida; Badruzsaufari Badruzsaufari (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2020)
Phylogenetic analysis of mangoes species using the nucleotide sequences of 5.8S rRNA genes aimed to determine the cladistics and evolution of kinship amongst the species of the genus Mangifera to support the conservation and breeding efforts of local endemics of South Kalimantan. The analysis involved 23 nucleotide sequences of the 5.8S rRNA gene obtained from the GeneBank of NCBI which were aligned and trimmed into 655 bp using MEGA X software. The Kimura-2 parameter model and  Maximum-Likelihood method used to construct a monophyletic tree of 4 clades. Clade I consists of M. torquenda, M. sumatrana, M. kemanga, M. quadrifida, M. griffithii, M. casturi, M. lalijiwa, M. macrocarpa, M. flava, M. gracilipes, M. pentandra and M. caloneura. Clade II consists of M. foetida, M. cochinchinensis, M. gedebe, M. oblongifolia, M. indica, M. laurina, M. sylvatica, and M. zeylanica. Clade III only consists of M. andamanica. Clade IV consists of M. odorata and M. camptosperma. The closest kinship occurred between M. odorata and M. camptosperma and the farthest kinship was M. camptosperma. M. andamanica has the farthest evolutionary distance with the longest branch.